NİETZSCHE'DE HAKİKAT VE PERSPEKTİVİZM - Nevzat Can (Felsefe Dünyası)
Nietzche who sees the world as a literary text that can be possibly be read through fragmentai writings. There are so many interpretations regarding the world, truths stated by these interpretations. The truth is not the thing one which to be found out and/or discovered. On the contrary, it is something that names the process necessary to create, and is to express the will of power. There is no way to make a distinction between Nietzche's views concerning the truth and perspectivizm. According to the perspectivist view, there are a lot of ways of tending towards the world and obtaining its knowledge. This stems from the plurality and diversity of the object inclined to taken. Those different perspectives of the world result in different group-formations by means of different concerns and values, and thus reveal different objects. Those different perspectives and views create many truths which cannot be reduced to each other and may even be opposite one to another. Depending on the variety of the interpretations, not just one dominant truth but also many different truhts will be possible